Unity or Divergence: Nahdlatul Ulama and Muhammadiyah Perspective on Interfaith Moderation - Aulia, Sulthonul; Maulana Fajrin, Ardhi; Ceesay, Abdoulie; Birkbeck, Musa Jallow (Al-Wasatiyah: Journal of Religious Moderation, 2024)
This study delves into the perspectives of Nahdlatul Ulama and Muhammadiyah members on the value of interfaith moderation in Indonesia. As the two foremost Islamic organizations, both play pivotal roles in shaping religious discourse and fostering harmony among diverse religious communities. Despite both organizations claiming adherence to Moderate Islam, this research identifies potential gaps between the conceptualization and grassroots implementation of these values. Differing interpretations arise, mainly due to the lack of a precise definition of "moderate." The research adopts a quantitative methodology, utilizing the Mann-Whitney U test to assess and compare the stance points of Nahdlatul Ulama and Muhammadiyah members across six dimensions of interfaith moderation. The findings reveal nuanced differences in stances, with notable distinctions in religious tolerance, social and cultural inclusiveness, and economic activities. However, both organizations share common values, emphasizing the importance of dialogue spaces for acknowledging differences and maintaining moderation values.